Hemostatic dressings made of oxidized bacterial nanocellulose membranes - Teixeira, Eugénia Cristina Queirós (2021)
Surgicel® (regenerated oxidized cellulose) is a bio-absorbable hemostatic material widely applied to prevent surgery-derived adhesions. Some critical issues have been reported associated with this biomaterial, which we aimed to overcome by producing bacterial nanocellulose (BNC) membranes with hemostatic activity, through electrochemical oxidation using the tetramethylpiperidine-1-oxyl (TEMPO) radical. Samples were characterized by FTIR, NMR, SEM, XRD and their degree of polymerization. The oxidation degree was evaluated by titration of the carboxyl groups and the hemostatic behavior by whole-blood-clotting assays. In vitro and in vivo biodegradability of oxidized BNC membranes were evaluated and compared with that of Surgicel®. The oxidation degree increased from 4% to 7% and up to 15%, corresponding to an applied charge of 400, 700 and 1200 Coulombs, respectively. The oxidized BNC preserved the crystallinity and the 3D nano-fibrillar network, and demonstrated hemostatic activity, although not as effective as that of Surgicel®. In vivo assays demonstrated that the oxidized membranes did not induce an inflammatory response, revealing a good biocompatibility. However, non-degraded oxidized BNC was still detected at the implantation site after 56 days.